Investigating the intersections of vulnerability detection and Internet of Medical Things (IoMT) in healthcare, a scoping review protocol for Remote Patient Monitoring (Research, Society and Development, 2024)
Due to the rapid and ubiquitous development and acceptance of IoT, healthcare providers have changed their locational settings from solely based in clinics to extend more broadly into the reach of patients’ domestic homes. This IoMT focus extends to various medical devices and applications within the healthcare domain, such as any form of smartphones, surveillance cameras, wearable sensors, and actuators, that hold the capability to access IoT technologies. The aim of this scoping review has two important objectives. The first is to understand the best approaches towards acquisition and refinement of data in favour of an optimised cyber security posture for remote patient monitoring. The second is to understand how best to detect cyberattacks and vulnerabilities in Medical IoTs using automated reasoning. The review will be carried out according to the Joanna Briggs Institute (JBI) scoping review methodology. The key information sources are Springer Link, IEEE Xplore, Science Direct, SCOPUS, and ACM databases. The search is limited to studies written in English. The initial step in the review uses keywords and index terms to identify literature from the selected database information sources. The second step then takes the identified elements and searches each of the databases. The third step involves a search of the references to determine literature inclusion using a full-text screening process. Medical IoT devices, specifically designed for patient monitoring and diagnosis, excel in their ability to collect, transfer, and interact with real-time data. It focuses on intersections between IoMTs, cyberattacks and vulnerabilities, knowledge graph detection, and automated reasoning.